Učinkovita uporaba ultrazvočne preiskave možganov v obdobju novorojenčka - Burja, Silva; Treiber, Milena; Tekauc Golob, Andreja (University of Maribor Press, 2019)
Effective use of cranial ultrasonography in the neonatal period. This manual is practical guide to ultrasound (US) diagnostics of congenital and acquired pathological changes in neonatal brain. The demonstration of normal US anatomy of neonatal brain and US characteristics of brain structures examinated through the four acoustic windows – using the anterior, posterior, mastoid fontanels and the temporal windows, follows to the description of elementary facts, about ultrasound and performance of good- quality cerebral US procedure. The second part of the manual deals with US images of different pathological changes with origin in the perinatal period – brain hemorrhages, dilatation of the liquor spaces,ischemical encephalopatie, brain malformations. Recommendations are given on the timing of US examination. The great majority of US images were performed at the neonatal units of the Maribor University Medical Center by the authors of this manual or one of their collegues. The last part deals with our experiences.